Genome Analysis of a Historical Shigella dysenteriae Serotype 1 Strain Carrying a Conserved Stx Prophage Region - Sváb, Domonkos; Falgenhauer, Linda; Horváth, Balázs; Maróti, Gergely; Falgenhauer, Jane; Chakraborty, Trinad; Tóth, István (Frontiers in Microbiology, 2021)
Shigella dysenteriae are significant agents of bacillary dysentery, accounting for a considerable number of illnesses with high morbidity worldwide. The Shiga toxin (Stx) encoded by a defective prophage is the key virulence factor of S. dysenteriae type 1 (SD1) strains. Here we present the full genome sequence of an SD1 strain HNCMB 20080 isolated in 1954, compare it to other sequenced SD1 genomes, and assess the diversity of Stx-prophages harbored by previously sequenced SD1 strains. The genome of HNCMB 20080 consists of a chromosome sized 4,393,622 bp containing 5,183 CDSs, as well as two small plasmids. Comparative genomic analysis revealed a high degree of uniformity among SD1 genomes, including the structure of Stx prophage regions, which we found to form two subgroups termed PT-I and PT-II. All PT-I strains are members of the sequence type (ST) 146 or ST260, while the only PT-II harbouring strain, Sd1617 proved to be ST untypeable. In accordance with data from previous reports, the Stx1 prophage could not be induced from HNCMB 20080. Our cumulative data do not support the notion that stx-harboring phages in STEC are derived from historical SD1 isolates.